2009
DOI: 10.1111/j.1365-2982.2009.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum 7α‐hydroxy‐4‐cholesten‐3‐one (or 7αC4), a surrogate test for bile acid malabsorption in health, ileal disease and irritable bowel syndrome using liquid chromatography‐tandem mass spectrometry

Abstract: Background Bile acid malabsorption (BAM) is reported in up to 50% of patients with functional diarrhea and irritable bowel syndrome with diarrhea (IBS-D). Serum 7α-hydroxy-4-cholesten-3-one (7αHCO, or 7αC4), an indirect measurement of hepatic bile acid synthesis, has been validated as a measurement of BAM relative to the 75SeHCAT retention test. Aim To develop a serum 7αC4 assay, normal values, and compare results from healthy controls, patients with ileal Crohn’s disease or resection, and patients with IBS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 32 publications
2
118
0
2
Order By: Relevance
“…Extraction recoveries for bile acids were quite similar to those reported for other existing methods [16][17][18]20,[22][23][24]. The extraction recovery for C4 was found to be approximately 62%, which was markedly lower than for bile acids and for other C4 methods [12,14,[25][26]. This is presumably explained by its lipophilic properties and by the fact that the others methods used different sample preparation techniques (protein precipitation, liquid-liquid extraction followed by SPE, derivatisation and salting-out respectively).…”
Section: Recoverysupporting
confidence: 75%
See 3 more Smart Citations
“…Extraction recoveries for bile acids were quite similar to those reported for other existing methods [16][17][18]20,[22][23][24]. The extraction recovery for C4 was found to be approximately 62%, which was markedly lower than for bile acids and for other C4 methods [12,14,[25][26]. This is presumably explained by its lipophilic properties and by the fact that the others methods used different sample preparation techniques (protein precipitation, liquid-liquid extraction followed by SPE, derivatisation and salting-out respectively).…”
Section: Recoverysupporting
confidence: 75%
“…Moreover, it is now well established that FXR activation by bile acids results in the regulation of various genes involved not solely in bile acid homeostasis but also in cholesterol, triglyceride and glucose metabolism [4][5][6][7][8][9]. Therefore, bile acids have gained much attention since they might be of interest as biomarkers or as pharmacological targets in several intestinal and metabolic conditions ranging from Crohn's disease to metabolic syndrome [5,[10][11][12].…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acid malabsorption (BAM) is generally not regarded as a cause of IBS. However, recent improvements in the techniques employed for assessing BAM have demonstrated that it may promote and contribute to a low-grade mucosal inflammation in IBS (Camilleri et al, 2009) and diarrhea in patients with inflammatory bowel disease symptoms (IBD) (Surawicz, 2010). Although the cell types that mediate these actions of BAs have not been identified, studies using neurotoxins and neurotransmitter antagonists suggest that BAs control motility and secretion through effects on the enteric nervous system (Alemi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%